Ecological adaptations and habitat functions of aquaculture biota in mangrove ecosystems: a critical review for sustainable management - Sucipto Sucipto (Lentera Negeri, 2026)
Mangrove ecosystems are highly productive coastal environments that provide important ecological functions for aquaculture biota through habitat complexity, nutrient availability, environmental stability, and natural protection from environmental disturbances. This review synthesizes current knowledge on the ecological characteristics and adaptive responses of aquaculture biota inhabiting mangrove ecosystems, as well as their implications for coastal adaptation and mangrove-based aquaculture development. A narrative synthesis approach was employed using scientific publications related to mangrove ecology, aquaculture systems, and coastal environmental management published between 2010 and 2025. A total of [XX] studies were reviewed, covering various tropical and subtropical mangrove ecosystems and focusing primarily on fish, crustaceans, and mollusks associated with aquaculture environments. The reviewed studies indicate that aquaculture biota in mangrove ecosystems possess adaptive characteristics that enable tolerance to fluctuating salinity, tidal dynamics, muddy substrates, and low dissolved oxygen conditions. Mangrove ecosystems also function as nursery grounds, feeding areas, and shelter habitats that support the growth and survival of aquatic organisms. In addition, mangrove vegetation contributes to nutrient cycling, sediment stabilization, and water quality maintenance, all of which are essential for aquaculture productivity. However, several studies reported contrasting findings regarding intensive mangrove-based aquaculture, particularly where poor environmental management and excessive land conversion reduced ecosystem resilience and biodiversity. This review is limited by variations in study design, geographic coverage, and species-specific data among the selected publications. Nevertheless, the synthesis highlights that mangrove-based aquaculture and silvofishery systems provide important opportunities to balance ecological conservation, coastal adaptation, and economic utilization in sustainable coastal development.